Effect of black pepper as natural feed additive on performance of guinea fowl - Azmi, Norazilah (2017)
Antibiotic growth promotion (sub-therapeutic) as feed additive has been practiced to maximize performance in poultry production. Researchers searched for alternatives to antibiotic growth promoters due to antibiotics resistance issues. The effect on addition of black pepper as natural feed additive on performance of guinea fowls was studied. The objective is to determine the effect of black pepper as natural feed additive as growth promoters in guinea fowl. A total of 45 keets at the age of three weeks were randomly divided into three treatment groups. Each group was further subdivided into three replicates at the rate of five keets per partitions in complete randomized design. The diet treatment were divided into three different diets namely Treatment 1 (T1) where the keets were fed with 100% commercial feed, Treatment 2 (T2) with commercial feed and 0.5% black pepper, and Treatment 3 (T3) with commercial feed and 1.0% black pepper. The experimental diets were fed for 12 weeks duration. Health of the stock and performance parameters was recorded. The results showed that, guinea fowl performance was not significantly influenced by addition of black pepper. However, there was difference between body weight gain, feed intake and feed conversion ratio for different treatment. T2 (0.5% black pepper) had significantly heaviest body weight gain compared to T1 and T3. The keets at T3 (1.0% black pepper) had significantly highest feed intake. Addition of black pepper in diet did not give effect on the morbidity and mortality of guinea fowl. All the keets were apparently healthy and no mortality was recorded during experiment. It was concluded that addition of black pepper as feed additive was not significantly (p< 0.05) improved on growth performance of guinea fowl.